(untitled) (LEARNing Landscapes, 2019)
Written from the perspective of a Grade 5/6 French Immersion teacher, this paper examines the role of music, poetry, and the visual arts in enhancing learner identity, in the context of the elementary school classroom. It begins with a focus on artistic metaphors that represent cultural and linguistic hyphenation. It then addresses practical applications of these metaphors into classroom activities, projects, and lessons, enhancing community, academic curricular goals, and student self-awareness.